Local food environments: Australian stakeholder perspectives on urban planning and governance to advance health and equity within cities. Issue 1 (2nd January 2018) - Murphy, Maureen; Jordan, Helen; Badland, Hannah; Giles-Corti, Billie
ABSTRACT: Urban planning policy has the potential to improve population health outcomes and reduce health inequities within cities. In Australia, however, the pathways for implementing policy approaches are unclear, and responsibilities are contested and dispersed across sectors, portfolios and levels of government. This study investigated government, non-government and private sector perspectives on spatial planning for local food environments and aimed to identify governance opportunities to advance healthy equitable food access. Informed by health governance frameworks, 27 key informant interviews with policymakers and practitioners from urban planning, public health, urban economic and partnership development were conducted in Melbourne, Australia, a city experiencing rapid growth. Stakeholders identified regulation, urban planning policy, finance, coordination and partnerships as key governance processes for the creation of healthy food environments; political leadership as a driver for action; and distributed leadership as essential for implementation. Urban health is a recurring theme in the UN Sustainable Development Goals with targets for health and wellbeing, and sustainable urbanisation. Our study contributes to an understanding of the governance actions required to deliver healthy equitable urban food environments, and demonstrates the importance of comprehensive action, particularly when two of the potentially most powerful levers, regulation and finance, are weak.